Rancangan Teknis Penambangan Emas pada PT DEF di Kecamatan Simpenan, Kabupaten Sukabumi, Provinsi Jawa Barat - Bagea Bagja Gumelar Gumelar; Iswandaru; Zaenal (UNISBA Press, 2022)
Abstract. PT DEF is a mining industry company engaged in gold ore mining which has a mining area in Simpenan District, Sukabumi Regency, West Java Province. Observations were made on the results of exploration drilling of 73 drill points in the form of recapitulation of drilling data which was used as a reference for making geological models and resource estimates. Based on the results of the grade assessment using the ordinary kriging method, the inferred resource was 166,482.38 tons with an average grade of 0.46 ppm, the indicated resource was 2,434,150.06 tons with an average grade of 0.58 ppm and the measured resource was 5,264,703.55 tons with an average grade of 0.85 ppm, so that the total resources obtained are 7,865,335.99 tons with an average grade of 0.76 ppm. Determination of areas that have the potential for mining is done based on the largest NPV value from the optimization pit results. Mining is carried out with an open-pit mining system, the mining method used is open pit. The design of the mine opening is made with a geometry of 6 m high, 5 m wide, and a slope of 52°. While the design of the road geometry used is a straight road width of 8.715 m, a bend road width of 14.84 m, a bend radius of 14.38 m, a superelevation of 40mm/m. Based on the results of the mining technical design, the mined reserves of gold ore were 7,270,393.62 tons with an average Au grade of 0.49 ppm. There are non-ore materials in the form of waste amounting to 9,190,104.22 Tons. The minimum gold ore production target is planned at 100,000 BCM/year. Abstrak. PT DEF merupakan perusahaan tambang yang bergerak pada komoditas bijih emas yang memiliki area pertambangan di Kecamatan Simpenan, Kabupaten Sukabumi, Provinsi Jawa Barat. Kegiatan Pengamatan dilakukan pada hasil eksplorasi pengeboran sejumlah 73 titik bor berupa rekapitulasi data pengeboran yang digunakan sebagai acuan pembuatan model geologi dan estimasi sumberdaya. Berdasarkan hasil penaksiran kadar menggunakan metode ordinary kriging, diperoleh sumberdaya tereka sebesar 166.482,38 ton dengan kadar rata-rata 0,46 ppm, sumberdaya terunjuk sebesar 2.434.150,06 ton dengan kadar rata-rata sebesar 0,58 ppm dan sumberdaya terukur sebesar 5.264.703,55 ton dengan kadar rata-rata sebesar 0,85 ppm, sehingga didapatkan total sumberdaya sebesar 7.865.335,99 Ton dengan kadar rata-rata sebesar 0,76 ppm. Penentuan area yang berpotensi untuk dilakukan penambangan dilakukan berdasarkan nilai NPV terbesar dari hasil pit optimasi. Penambangan dilakukan dengan sistem tambang terbuka, metode penambangan yang digunakan yaitu open pit. Rancangan bukaan tambang dibuat dengan geometri tinggi jenjang 6 m, lebar 5m, dan kemiringan 52°. Sedangkan rancangan geometri jalan yang digunakan yaitu lebar jalan lurus 8,715 m, lebar jalan tikungan 14,84 m, jari-jari tikungan sebesar 14,38 m, superelevasi 40mm/m. Berdasarkan hasil rancangan teknis penambangan, diperoleh cadangan tertambang bijih emas sebesar 7.270.393,62 Ton dengan kadar rata-rata Au 0,49 ppm. Terdapat material bukan bijih berupa waste sebesar 9.190.104,22 Ton. Target produksi minimal bijih emas direncanakan sebesar 100.000 BCM/tahun.